Relevance of Farmers’ Cultivation of Jatropha Plant for Sustainable Environment in Lagelu Community Oyo State - Adebayo Samson Adeoye; Oluwole Olalekan Oke; Michael Omokhafe Smart (Indonesian Journal of Social and Environmental Issues (IJSEI), 2021)
The unabating environmental degradation from heavy consumption of fossil fuel and chemicals by the masses has compelled the potential use fullness of Jatropha plant to engender a sustainable environment. This study examined the relevance of farmers’ cultivation of Jatropha plant for sustainable environment in Lagelu community Oyo State. A simple random sampling technique was used to select 120 Jatropha farmers from 175 trained farmers in the study area. Data collected were analyzed using both descriptive and inferential statistics. Results revealed that the majority (66.7%) were males, married (90%), possession of formal education (91.7%), and had various livelihood activities (86.7%). There was a significant association between the personal characteristics of the respondents and Jatropha cultivation for the sustainable environment. There was also a correlation between the cultivation management practices engaged by farmers and the relevance of farmers’ cultivation of Jatropha plant for the sustainable environment (r=0.453, p≤ 0.05). The study further revealed that there was a correlation of relevance of farmers’ cultivation of Jatropha for sustainable environment in the study area. Therefore, the government and non-government organizations should encourage the development and massive cultivation of Jatropha through awareness and provision of credit facilities for farmers to engender a sustainable environment.